SAT0049 21st century state of rheumatoid arthritis management in the uk. (15th June 2017) - Tan, AL; Buch, M; O'Reilly, D; Sheeran, T; Bishop-Bailey, A; Nock, G; Chitale, S; Emery, P
Abstract : Background: The rheumatoid arthritis (RA) Treat to Target (T2T) recommendations 1 defined in 2010 aimed to support clinicians to achieve optimal therapeutic outcomes for their patients. Objectives: 38 hospitals prospectively audited management of newly diagnosed RA patients to determine compliance with the T2T recommendations and therapeutic outcomes achieved. Methods: From April 2012 to September 2016 and upon diagnosis of RA, data on disease history, management and clinical outcomes were collected prospectively in a web based tool. Follow up to date provides data for up to 24 months from diagnosis (baseline). Results: 1571 patients were recruited in 38 centres, with 12 months' follow up for 713 patients and of these 269 also had 24 months' follow up. 1021 (65%) patients were female and 1360 (87%) had a treatment target documented at baseline (1235 [79%] disease activity score 28 (DAS28) remission and 125 [8%] low disease activity state (LDAS)). DAS28 remission is defined as DAS28 <2.6, LDAS is defined as DAS28 ≥2.6<3.2. Median baseline DAS28 scores were 4.9 and 5.3 for patients having a DAS28 remission and LDAS target, respectively. The table shows DAS28 scores at baseline, 12 and 24 months, and disease management received for the subset of patients with available DAS28 scores at the relevant time points, stratified by those who did/did not achieve their remission target and those with/without sustained remission at 24 months. Of the 108 patients eligible to receive biologic therapy, according to NICE guidance, 39 (36%) received a biologic within their first 24 months of treatment. Conclusions: The results suggest that more patients with a target set at baseline are in remission at 12 months and at 24 months than those without a target set. Number of visits, number of DAS28 scores and starting dual therapy within 6 months do not appear to affect the proportion of patients in remission at 12 months, but active management in the first 12 months (>4 visits, >4 DAS28 scores) does appear to be associated with more patients in remission at 24 months. Thus we conclude that treating RA early and aggressively, in line with the T2T guidelines, leads to sustained clinical improvement. References: Smolen et al. Treating rheumatoid arthritis to target: recommendations of an international task force. Ann Rheum Dis 2010;69:631–637. Disclosure of Interest: A. L. Tan Consultant for: I have received honoraria from AbbVie Ltd., M. Buch Consultant for: has received previous honorarium/consultancy with Abbvie, Astra Zeneca, Bristol-Myers Squibb, Lilly, Roche-Chugai, Sandoz and research grants from Roche and Pfizer., D. O'Reilly Consultant for: has been paid research/consultancy fees/other honoraria by Amgen, Abbvie, MSD, pH Associates, Roche, UCB and Wyeth., T. Sheeran Consultant for: has been paid consultancy fees by Roche, AbbVie, Novatis and Pfizer., A. Bishop-Bailey Employee of: I am an employee of pH Associates, the company commissioned by Abbvie to design and implement the study, as well as perform analysis and presentation/publication of the study data., G. Nock Employee of: I am an employee of pH Associates, the company commissioned by Abbvie to design and implement the study, as well as perform analysis and presentation/publication of the study data., S. Chitale Consultant for: has been on an advisory board for Abbvie and Pfizer, and has received educational grants from Abbvie, Pfizer and UCB., P. Emery Consultant for: undertaken clinical trials and provided expert advice to Pfizer, MSD, Abbvie, BMS, UCB, Roche, Novartis, Samsung, Sandoz and Lilly